Quantifying CO2 Emissions From Individual Power Plants From Space. Issue 19 (13th October 2017) - Nassar, Ray; Hill, Timothy G.; McLinden, Chris A.; Wunch, Debra; Jones, Dylan B. A.; Crisp, David
Abstract: In order to better manage anthropogenic CO2 emissions, improved methods of quantifying emissions are needed at all spatial scales from the national level down to the facility level. Although the Orbiting Carbon Observatory 2 (OCO‐2) satellite was not designed for monitoring power plant emissions, we show that in some cases, CO2 observations from OCO‐2 can be used to quantify daily CO2 emissions from individual middle‐ to large‐sized coal power plants by fitting the data to plume model simulations. Emission estimates for U.S. power plants are within 1–17% of reported daily emission values, enabling application of the approach to international sites that lack detailed emission information. This affirms that a constellation of future CO2 imaging satellites, optimized for point sources, could monitor emissions from individual power plants to support the implementation of climate policies. Plain Language Summary: Burning coal for electricity generation accounts for more than 40% of humanity's current global CO2 emissions. To better manage CO2 emissions, improved methods of quantifying emissions are needed at all spatial scales. Although the Orbiting Carbon Observatory 2 (OCO‐2) satellite was not designed for monitoring power plant emissions, we show that in select cases, CO2 observations from OCO‐2 can be used to quantify daily CO2 emissions from individual middle‐ to large‐sized coal power plants by fitting the data to a simple model. Demonstrating the method on U.S. power plants with reliable reported emission data enabled application of the approach to international sites that have less or lower quality information available on emissions. Space agencies around the world are currently exploring how to design satellite missions to help address climate change and support Monitoring, Reporting and Verification (MRV) of CO2 emissions for climate agreements. This work affirms that a constellation of CO2 imaging satellites, with a design optimized for point sources, could monitor CO2 emissions from individual fossil fuel burning power plants to support that objective. Key Points: The combustion of coal for electricity generation accounts for more than 40% of global anthropogenic CO2 emissions Orbiting Carbon Observatory 2 observations can be used to quantify CO2 emissions from individual coal power plants, in selected cases This work suggests that a future constellation of CO2 imaging satellites could monitor fossil fuel power plant CO2 emissions to support climate policy